Kajian Evaluasi Pengoperasian Angkutan Pemadu Moda Di Bandara Hang Nadim Batam - Sinaga, Rosita; Rita, Rita (Warta Penelitian Perhubungan, 2012)
Ha11g Nadim Airport began operations on August 9, 1965, located in Big Stone area about 20 km from downtown Batam can accommodate 18 (eighteen) wide-bodied aircraft like Boeing 767 and has the lo11gest runway in Indonesia which is 4025 meters. Movement of passengers 011 merage 6,000 people/day, with 42 flights/day. To improve air transport services after getting of the plane tawards the ultimate goal, the Hang Nadim Airport in cooperation with PT. Dmnri in order to improve services, especially for passenger air transportation that will melajutkan journey towards the ultimate goal in Batam that is by adding alloying modes of transport other than taxis and motor vehicle (motorcycle taxis). Damri buses started operating on December 5, 2008, and is still running but not according to what was expected because as the location of parking too far from the gate making it difficult for passengers to board buses and schedules refe1Ted to (headway) and things that can diapstikan this is because the number of bus fleet is too small. To peninkgatan services necessary to the addition of the bus fleet and the addition of routes I new routes, especially to human settlements in the area of Batam.